Magnetic resonance imaging after laparotomy of fetal evacuation in advanced abdominal pregnancy - Erien Pradyta; Tri Wulanhandarini; Manggala Pascawardhana (Radiology Case Reports)
Abdominal pregnancy (AP) is a rare event of globally reported pregnancy and is significantly challenging to diagnose because of various symptoms. Therefore, we aimed to present a case of a 26-year-old female with unexpected AP of third pregnancy found during emergency fetal evacuation laparotomy. The possible scenario was found to be fetus implanted into the fibroid scar of her obstetric history, leading to complications with uterine rupture. The image was observed properly by the MRI that was performed after the laparotomy. Although the ultrasound was used as the diagnostic tool for the AP, the MRI had an excellent ability to show detailed anatomy as a reliable imaging modality for patients with complicated obstetric history.